Effect of Acute Cold Exposure on Differential Expression of Tissue D-I and D-II Iodothyroinine Deiodinase [T4-5’-Deiodinase] Activity in Congenic Lean and Obese LA/Ntul//-cp Rats: Iodothyroinine Deiodinase Activity in Obese Rats - Tulp, Orien L; Sainvil, Frantz; Awan, Aftab; Rizvi, Syed A. A (European Journal of Applied Sciences, 2025)
Thyroid hormones are known to play a critical role in metabolic adaptation to chronic changes in diet and environment. The prohormone tetraiodothyronine (T4) is converted to the active form, triiodothyronine (T3) in peripheral tissues via actions of outer ring deiodination by D-I or D-II isoforms of T4-5’ deiodinase activity. In contrast, T4 may also become inactivated during periods of caloric depravation via an inner tyrosyl ring D-III deiodinase to form an inactive hormone, 3’5’3 triiodothyronine, or ‘reverse T3’ (rT3). Measures of D-I and D-II were determined in selected tissues obtained from congenic adolescent lean and obese female LA/Ntul//-cp rats when 16 weeks of age following laboratory temperature exposure of 22°C or 14 hours acute cold exposure at 4°C. Circulating T4 concentrations were similar in lean and obese rats and serum T3 but not T4 concentrations increased dramatically in both phenotypes following the cold exposure, consistent with phenotype- and maximal tissue-linked changes in outer ring T4-5’-deiodinase activity / mg tissue protein and per depot. In Gastrocnemius muscle, only D-II was detected, and gastrocnemius D-II activity of obese increased modestly following cold exposure. In Liver, Kidney, and IBAT and in cold-induced temperature exposure linked increases in IBAT deiodinase activity / mg tissue protein in this strain, but when D-I and D-II deiodinase activity were computed / tissue mass however further analysis indicated that D-I was the predominating adaptive deiodinase in liver, kidney, and gastrocnemius muscle, while in IBAT D-II > D-I activity / IBAT depot and was greater in obese than lean rats. Cold exposure was associated with modest increases in net deiodinase activity only in kidney. Thus, the cold induced increases in circulating T3 in lean and obese rats following cold exposure are likely attributed at least in part to modest increases in IBAT outer ring T4-5’ D-II and renal D-I deiodinase activity, in addition to likely attaining maximal rates of conversion in other peripheral tissues in addition to possible combination with decreases in hormone clearance rates and enhanced receptor occupancy during cold induced stress, and where they contribute to protective measures during dietary or environmental stress.